Responses of the macrobenthic community to cage culture in one tropical lagoon in the South China Sea. (July 2022) - Ge, Changzi; Wang, Linan; Zhang, Yuqun; Qu, Chunfeng; Liu, Xu; Zhu, Lixin; Song, Jianda; Zheng, Fengying; Li, Linwei; Liu, Wenshuang; Zheng, Yajuan
Highlights: Marine geomorphology, fishing and cage culture jointly affected macrobenthos. Cage culture did not inevitably reduce diversity of macrobenthos. Biomass and abundance of macrobenthos might be improved by cage culture. Stability of macrobenthic community might be promoted by cage culture. Abstract: Macrobenthos have been used to monitor the self-pollution of cage culture. Will cage culture inevitably reduce their biomass and biodiversity? A one-year investigation was conducted in a lagoon with a history of cage culture for approximately 20 years. In December, the macrobenthos biomass in cage culture area (CCA) was higher than that in FTA (area farthest from CCA). The macrobenthos biodiversity in CCA and NCA (area near CCA) was higher. During the production period, the stabilities of the microbenthic communities in NCA and FRA (area further from CCA) were lower. In the nonproduction period, the stability of the macrobenthic community in CCA was higher than that in FTA. The landform, fishing and organic matter and Ex-P (exchangeable phosphorus) in sediments jointly affected macrobenthos. Cage culture did not inevitably reduce macrobenthos biomass and biodiversity but provided stable microhabitats for macrobenthos. The NCA and FRA may be ecotones between CCA and FTA.